Carreira docente móvel em administração: o professor sedentário nômade? - Passos, Janduhy Camilo (2013)
Mobility is a social phenomenon, complex and intrinsic to human life, for it gathers from economic to cultural and affective elements and imaginary space for individuals and groups. Under this approach, it is clear that, at present, in addition to having unique characteristics, in line with the economic and social transformations of the twentieth century, mobility has assumed importance as a field of study, leading several researches because of the dramatic human displacement on geographical space motivated by professional reasons. Therefore, this thesis has as its object of investigation the phenomenon of mobility and aimed to examine, through the concept of mobile career, its implications on personal and professional teachers experience who works in business Schools, taught at a University in the cities affected by Uberlândia / MG, the hub educational Triangulo Mineiro and Alto Parnaíba. We observed that, to fulfill their professional activities, these teachers are subject to mobility, because living in Uberlândia, but perform continuous displacements across the cities affected by that county , promoting meetings in diverse cultural contexts and frequent interactions with social situations and diverse organizational, which leads to our research question is: what are the implications of mobility on the personal and professional lives of business teachers, who lives in Uberlândia/MG and works at university at cities that are under the influence of this educational hub? This is a qualitative study, guided by the interpretive paradigm, and data were collected through interviews, and subjected to content analysis. The results show that the Mobile teaching career brings positive consequences, such as allowing the teacher supercharge their resume and develop teaching skills, aspects that later allows his admission in Public Institutions. Mobility also contributes to teachers to improve their relationship skills, flexibility to adapt to intercultural contexts, and promote the establishment of new social and professional network. However, the frequent shifts enhance the teacher's work, collaborate for the removal of their family, damage their health and compromise the overall quality of their life.